The 18H2N4MA steel strength characteristics increase = Повышение прочностных характеристик стали 18Х2Н4МА - Dubovoy, A. N.; Дубовой, А. Н.; Volkov, G. V.; Волков, Г. В.; Zhdanov, A. A.; Жданов, А. А. (My University, 2015)
The article considers the impact of prerecrystallization heat treatment on the hardness, strength and fatigue strength of the 18H2N4MA steel after preliminary shot blasting. It is experimentally established that as the result of prerecrystallization heat treatment at 500 °C with 3 minutes delay the layer with an increased measure of hardness (hardness is increased by 42 %) is formed on the 18H2N4MA steel surface after the preliminary shot blasting. The 18H2N4MA steel shot blasting causes the formation of compressive stresses in the surface layer, the subsequent prerecrystallization heat treatment does not change the nature of the residual stress, but only leads to the decrease in the absolute values, preserving the work-hardened layer depth. The prerecrystallization heat treatment leads to an increase in fatigue strength of the 18H2N4MA steel about 2.7 times compared with the shot blasting and increase of the tensile strength by 11 %, with plasticity indexes substantially constant. Such an increase in the strength indicators of the 18H2N4MA steel as a result of prerecrystallization heat treatment is caused by the formation of the substructures with shredded precinct in the steel surface layer. The given assumption is confirmed by the X-ray diffraction and electron metallography results. After prerecrystallization heat treatment the partial subgrains grinding from 222 ÷ 133 nm after shot blasting to 90 ÷ 49 nm is observed in the 18H2N4MA steel structure. = Исследовано влияние предрекристаллизационной термической обработки на предел прочности, твердость и усталостную прочность стали 18Х2Н4МА после дробеструйной обработки.
Дубовой, А. Н. The 18H2N4MA steel strength characteristics increase = Повышение прочностных характеристик стали 18Х2Н4МА / А. Н. Дубовой, Г. В. Волков, А. А. Жданов // Shipbuilding & Marine Infrastructure. – 2015. – № 1 (3). – C. 122–130.
Keywords: plastic deformation; recrystallization heat treatment; fatigue strength; hardness; substructure; пластическая деформация; предрекристаллизационная термическая обработка; прочность; твердость; усталостная прочность; субструктура